Audit Pricing of Shared Leadership. Issue 2 (26th January 2018) - Choi, Youn-Sik; Hyeon, Jiwon; Jung, Taejin; Lee, Woo-Jong
ABSTRACT: This study explores audit implications of shared leadership in client firms. Analyzing data from 2002 to 2013 of Korean listed companies, we find that auditors spend fewer audit hours and charge lower audit fees for clients with multiple CEOs. Additional tests reveal that the lower audit fees for co-CEO clients are likely attributable to reduced audit effort rather than to reduced hourly rates. We also document that firms with co-CEOs exhibit better-reporting quality than do firms with a solitary CEO. In sum, this article presents evidence that mutual monitoring via co-CEO appointments assures high-quality financial reporting of audit clients, and thus leads to reduced audit fees.